2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--35687
|View full text |Cite
|
Sign up to set email alerts
|

Work in Progress: Studying the Factors Affecting Women Recruitment and Retention in Engineering

Abstract: She previously was on the faculty of Mechanical Engineering in the Henry M. Rowan of College of Engineering, Rowan University, Glassboro, NJ for 20 years. She has been an active member of ASEE since 1998. She joined as a graduate student, after working on an engineering education project and presenting that work and student chapter activities at annual conference. As a faculty member, she regularly publishes and presents at the ASEE Annual Conference. Her interests are in design education and assessment in mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Outreach programs have shown to improve self-esteem as well [46], [47]. A study by Delahanty & Silverman found that having strong mentors was an important factor in improving creative self-efficacy [48], and mentorship has been shown to be important to the retention of women more broadly [49], [50]. Additionally, targeted training in spatial reasoning and strategy has been found to contribute to selfconfidence in engineering, especially for women [26], positioning this training to potentially improve both spatial reasoning skills and self-efficacy at once.…”
Section: Self-efficacy Of Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outreach programs have shown to improve self-esteem as well [46], [47]. A study by Delahanty & Silverman found that having strong mentors was an important factor in improving creative self-efficacy [48], and mentorship has been shown to be important to the retention of women more broadly [49], [50]. Additionally, targeted training in spatial reasoning and strategy has been found to contribute to selfconfidence in engineering, especially for women [26], positioning this training to potentially improve both spatial reasoning skills and self-efficacy at once.…”
Section: Self-efficacy Of Individualsmentioning
confidence: 99%
“…Beyond specific course designs and outreach programs, the literature reveals some general considerations for increasing accessibility of engineering and CAD technology for women. Osta et al in 2020 studied the main factors influencing the retention of women in engineering, and found that supportive family and friends, mentorship, coursework, career goals, internships and research opportunities, pre-college experience, and support professors/staff were found to be the main factors [50]. Amelink & Meszaros in 2011 also found that faculty interaction in the classroom, particularly receiving feedback and being treated with respect, was an important consideration in retention of females in engineering [49].…”
Section: Area Of Improvement: General Engineeringmentioning
confidence: 99%